Kansas farmers market assessments: an internship at the Kansas Department of Health and Environment - Steele, Patrick (My University, 2014)
The Kansas Department of Health and Environment focuses on the health and wellness of Kansas residents through multiple factors of health promotion. This report will focus on an internship at the Department of Health and Environment. The paper will focus on the internships two primary objectives: Kansas Farmers Market dot survey, and the Physical Activity Championship Guide. The Kansas Farmers Market dot survey was created to assess customer’s perception of the farmers market, and to analyze spending’s as well as motivational factors to attend and shop at local farmers markets. This includes a review of literature about the benefits farmers markets can provide to customers. The Physical Activity Championship toolkit provides resources and networking for physical activity innovators across all counties in the state of Kansas. The toolkit includes large amounts of resources for promoting physical activity in communities across multiple social ecological levels, ranging from the individual to policy level interventions. Real world experience provided exceptional education experience and allowed application of class knowledge in a state health level setting.
Keywords: Farmers Market; KDHE; Physical activity championship toolkit; Public Health (0573)